Post-COVID-19 sino-orbital mucormycosis: a case report - Chaudhary, Mahesh Kumar; Baranwal, Chandan; Pant, Rajesh; Chhetri, Sujan Singh; KC, Toran; Aryal, Gopi (Nepal Mediciti Medical Journal, 2022)
Mucormycosis is an invasive fungal infection caused by fungi of the order Mucorales. Mucorales fungi are ubiquitous in environment in association with decaying organic matter. Here we report the case of a 68-year old female who presented with history of ptosis of the left eye with decreased vision, facial pain and loss of sensation in the left cheek. She had history of COVID-19 infection. Magnetic resonances imaging of the brain revealed intense enhancement of left optic nerve. Bilateral spenoidal, ethmoidal and left maxillary sinus showed mucosal thickening. Histopathological and microbiological examination of the specimen confirmed the case of invasive mucormycosis. Despite treatment, patient died at 7th day of hospitalization.